Mineralized Cartilage and Bone-Like Tissues in Chondrichthyans Offer Potential Insights Into the Evolution and Development of Mineralized Tissues in the Vertebrate Endoskeleton - Atake, Oghenevwogaga J.; Eames, B. Frank (Frontiers in Genetics, 2021)
The impregnation of biological apatite into the extracellular matrix, a process termed biomineralization, gives rise to diverse mineralized tissues in vertebrates. Preservation of mineralized tissues in the fossil record has provided insights into the evolutionary history of vertebrates and their skeletons. However, current understanding of the vertebrate skeleton and of the processes underlying its formation is biased towards later-diverged groups, such as the tetrapods mouse and chick. Chondrichthyans (sharks, skates, rays, and chimaeras) are the earliest-diverged extant (living) vertebrate group with a mineralized skeleton, potentially offering unique insights into skeletal evolution. For example, bone is a vertebrate novelty, but the internal supporting skeleton (endoskeleton) of extant chondrichthyans is commonly described as lacking bone. Challenging this notion, subperichondral tissues in the endoskeleton of some chondrichthyans display mineralization patterns and histological and molecular features of bone. Additionally, the chondrichthyan endoskeleton demonstrates some unique skeletal features and others that are potentially homologous with other vertebrates, including a polygonal mineralization pattern, a trabecular mineralization pattern, and an unconstricted perichordal sheath. Because of the basal phylogenetic position of chondrichthyans, developmental and molecular studies of chondrichthyans are critical to flesh out the evolution of vertebrate skeletal tissues, but only a handful of such studies have been carried out to date. This review discusses morphological and molecular features of chondrichthyan endoskeletal tissues and cell types, ultimately emphasizing how comparative embryology and transcriptomics can reveal homology of mineralized skeletal tissues (and their cell types) between chondrichthyans and other vertebrates.